A Relationship Between Resilience and Mental Health Among Covid-19 Survivors - Priyanka Verma; Sandeep Singh (International Journal of Behavioral Sciences, 2025)
In 2020, COVID-19 first appeared in Wuhan, China. Covid-19 affects the world at the global level. This pandemic disrupted lives and communities by having a significant negative impact on people's physical and mental health. Resilience helps individuals to bounce back from the crisis. The study examines the connection between COVID-19 survivors' mental health and resiliency. A sample of 100 people, 50 of whom were men and 50 of whom were women, between the ages of 30 and 50, was examined. Some measures have been used such as the Resilience scale by Wagnild and Young (1993) consisting of 25 items and the Mental Health Inventory by Veit and Ware (1983) consisting of 18 items. Resilience and mental health were found to be significantly positively correlated by statistical tests, including an independent t-test and product moment correlation. Research indicates that resilience lowers psychological suffering in addition to improving mental health. Additionally, gender variations were noted, with men scoring higher on mental health measures and women showing better resilience levels. These findings emphasize how crucial it is to build resilience in order to support mental health, especially in times of international health emergencies. Future studies could examine other variables affecting this association in a variety of demographics.
Keywords: COVID-19 first appeared in Wuhan; China. Covid-19 affects the world at the global level; In 2020